Kapabilitas Proses Pelatihan Metode Statistika bagi Mahasiswa Pendidikan IPS Universitas Negeri Malang: Capability Process Analysis of Statistical Methods Training for Students of Social Science Education, Malang State University - Lucia Ari Dinanti; Zakiatul Wildani; Sri Pingit Wulandari; Wahyu Wibowo; Mike Prastuti; Iis Dewi Ratih (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Statistical methods are required as a tool for data analysis in student-led research projects, such as thesis/final projects. However, many students, particularly those from the Faculty of Social Sciences, Department of Social Studies Education, State University of Malang (FIS-UM), do not comprehend statistical methodologies yet. One way to overcome this problem is to conduct data analysis training on statistical methods. For this reason, the Quality and Productivity Engineering Laboratory, Department of Business Statistics, Faculty of Vocational, ITS, organized a community service program in the form of training for Social Science Education students. Initially, this program was planned to be held using a combination of online and offline training. However, the program was carried out using only online training because of some restrictions on community activities in Java and Bali. In this case, six materials are offered with software practice and assignments. The movement had 202 participants from three batches: 2018, 2019, and 2020. However, participants from batch 2018 can not finish the training due to some reasons. The average learning score (RHB) for the class of 2020 was 84.56, while the RHB for the class of 2019 was 80.85. There was no significant difference in RHB between these two groups using the t-test at a significance level of 5%. In addition, the training process of batch 2020 is capable since the X and MR charts of average learning scores demonstrate a controlled process, with a capability index of 1.55.